Estudio de la satisfacción laboral de los servidores públicos del gobierno descentralizado de la parroquia Quiroga - Montesdeoca Cajape, Angie Jamileth (2022)
This research was developed from job satisfaction and performance, these variables being responsible for the degree of productivity and institutional commitment that the collaborators of an institution have. The study had the objective of evaluating the job satisfaction of the servants of the Decentralized Autonomous Government in Quiroga parish (GADPR Quiroga) to verify the factors that affect the performance of their functions. For the determination of the objective, information collection tools were first applied, which include a structured interview applied to the direction of the entity and a construct of questions structured through dimensions and indicators with Likert scales, later for the determination of the correlation between variables spearman's Rho was used with a Shapiro Wilk data normality test, finally, the matrix of the improvement plan for the approach of corrective actions was designed. The results obtained through the application of the methodology show unfavorable factors in the dimensions of Job, Training, Motivation and Quality of Service, likewise Spearman's Rho yielded a correlation coefficient of 0.177 establishing the existence of a very weak correlation between the study variables, with a bilateral significance of 0.603 being this greater than that stipulated 0.05 dismissing the general hypothesis considered in the present tool. The unfavorable factors detected can lead to low productivity and have an impact on the services provided by the institution to society.